FACTORS INFLUENCING THE MAINTENANCE OF STATIC AND DYNAMIC EQUILIBRIUMS - Tuychieva Dildora Turgunovna (Modern American Journals, 2025)
Balance beam exercises are one of the most challenging events in women's gymnastics, where maintaining body stability plays a crucial role in conditions where the ability to restore it through physical strength is extremely limited, and where the only "weapons" are precision of movement and a subtle sense of balance.